PENERAPAN METODE RETINEX UNTUK MENINGKATKAN KECERAHAN CITRA PADA HASIL SCREENSHOT - Soeb Aripin; Guidio Leonarde Ginting; Natalia Silalahi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2017)
Improved quality is required because often the image tested has poor quality, one of which is image enhancement using Retinex method where Retinex is a technique used to get a new image with better contrast than contrast from its original image.There are four main stages to be done To obtain a new image up to the process of displaying image statistics, ie the process of displaying the initial image in the window, improving the image contrast, displaying the image histogram and display the image statistics. Quality improvement is required because the image on the screenshot has poor quality, By improving image quality using Retinex method. This Retinex method is a method used to get a new image with better contrast than the contrast of its original image.